DOWNREGULATION OF TNF-α, NF-κB p65, COX-2 AND iNOS BY β-SITOSTEROL AMELIORATE THE TOXIC EFFECT OF Fe-NTA ON RENAL TISSUE - R. SHARMILA; G. SINDHU (International Journal of Pharma and Bio Sciences, 2016)
The success of dysregulated NF-κB activated genes inhibition by phytosterols has encouraged in targeted therapy of chronic inflammatory diseases. The objective of this current study was to examine the involvement of β-sitosterol in the inflammatory cascade against renal carcinogen. Renal cancer was induced by single intraperitoneal injection of N-diethylnitrosamine (200 mg/kg bw) and twice weekly administration of ferric nitrilotriacetate (9 mg Fe/kg bw) for 16 weeks. The chemopreventive potential of β- sitosterol against renal carcinogen was studied in terms of inflammatory markers. Our study showed that oral administration of β-sitosterol (20 mg/kg bw) pretreatment significantly (p < 0.05) downregulated the expression of inflammatory markers which have been modified by Fe-NTA. We found that, the renal protective effect of β-sitosterol is associated with the inhibition of the inflammatory cascade through the down regulation of NF-κB activation, TNF-α, iNOS and COX-2 production. Antiinflammatory property of β- sitosterol could provide the link to understand its chemopreventive mechanism in experimental carcinogenesis.